Fenomena Penolakan Jenazah Covid-19 Perspektif Hadis di Indonesia - Sari, Maula; Wahid, Abd (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The phenomenon of rejection of Covid-19 corpses is rife at the moment. Prophet Muhammad never refused the corpse who died from a virus or years. The instructions from the Messenger of Allah in the management of the body should follow the ways of burial, because it was feared the stench, and became wild animal food. But some people still refused the burial of Covid-19' corpses because of the pretext of excessive fear with the virus. Whereas in Islam the body must be accepted with pleasure and treated well. However, what happened in some cases, the people were afraid of receiving the corpses. It also happened when they wanted to be buried. Furthermore, some rejected the body and the medical team who wanted to bury it. This paper discusses the phenomenon of the rejection of the corpses of Covid-19 from the perspective of the hadith. The research in this qualitative paper is a type of library research with a hadith contextualization approach. It can be concluded that, first, it is not justified to reject the corpses of Covid-19 because the Messenger of Allah never rejected the body due to the plague and they have the privilege of martyrdom in the afterlife. Second, the solution to the rejection of the body is to continue to administer the body following government protocols and always follow the Shari'a to avoid all martyrdom.